Biogenic Supported Lipid Bilayers from Nanosized Extracellular Vesicles. Issue 4 (26th February 2018) - Montis, Costanza; Busatto, Sara; Valle, Francesco; Zendrini, Andrea; Salvatore, Annalisa; Gerelli, Yuri; Berti, Debora; Bergese, Paolo
Abstract: Fabrication of synthetic surfaces that reproduce structure and function of biological membranes is an open challenge. This work reports the first example of supported lipid bilayers obtained from extracellular vesicles (EVSLBs). EVSLBs harness and pattern in two dimensions key properties of extracellular vesicle (EV) membranes, which present intermediate complexity between synthetic mimics and natural membranes and innate link to phenotype and function of the originating cells. Silica‐supported EVSLBs are formed from nanosized EVs—separated from culture media of prostate cancer model TRAMP‐C2 murine cells—following a characteristic crowding‐fusion pathway. They display peculiar properties at different length scales, such as 2.5 nm roughness, lipid‐raft‐like domains, and cushioned patches (with the cushion filled with the native EV biomolecular cargo), which preserve the native EV membrane orientation with the proto‐oncogene tyrosine‐protein kinase Src (c‐Src) accessible to antibody recognition. Abstract : Supported lipid bilayers from extracellular vesicles (EVs) are fabricated for the first time. By projecting in two dimensions key properties of EV membranes laced with a link with the originating cell biology, these biogenic surfaces may contribute to progress breakthrough "surface biotechnologies, " such as cell manipulation and organoid‐on‐a‐chip.